Emendamenti a Svetonio - Lucarini, Carlo M. (Hyperboreus, 2015)
The aim of this paper is to shed new light on the textual problems in about ninety passages of Suetonius’ De vita Caesarum; in many cases I propose new conjectures, but sometimes I try to defend the paradosis or to strengthen conjectures already suggested by other philologists.